Effect of the nano-oxide layer as a Mn diffusion barrier in specular spin valves - Jang, SH; Kang, T; Kim, HJ; Kim, KY (AMER INST PHYSICS, 2002)
In previous work an enhanced giant magnetoresistance (GMR) effect in spin valves (SVs) with a nano-oxide layer (NOL) after annealing at about 250-300 degreesC has been reported. We have shown that SVs with a NOL also have higher thermal stability of the MR ratio at 300 degreesC. From secondary-ion-mass spectroscopy and x-ray photoelectron spectroscopy depth profile analysis, the mechanism of the improved thermal stability of the SVs with a NOL is shown to be related to MnO formation within the NOL. Thus, Mn atoms from the FeMn layer are trapped, and Mn diffusion is inhibited by the NOL during annealing. (C) 2002 American Institute of Physics.
Keywords: MAGNETORESISTANCE; ENHANCEMENT